Selectivity of the herbicides sethoxydim, isoxaflutole and bentazon on native tree species - Brancalion, Pedro Henrique Santin; Isernhagen, Ingo; Machado, Ronan Pereira; Christoffoleti, Pedro Jacob; Rodrigues, Ricardo Ribeiro (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the sensitivity of native tree species used in the recovery of degraded land to the herbicides sethoxydim, isoxaflutole and bentazon. The species studied were Senna multijuga, Guazuma ulmifolia and Croton urucurana, and the treatment applied comprised one control sample (no herbicides were applied) and the application of the herbicides at one fourth, half, one, two and fourfold the recommended dose (sethoxydim: 184 g ha-1, isoxaflutole: 37.5 g ha-1, bentazon: 720 g ha-1). Phytotoxicity symptoms, growth in length, increase in leaf number, and leaf dry mass were evaluated. In another experiments, the recommended doses of the same herbicides were applied to other 22 native tree species, for which the leaf dry mass was evaluated. The experiments were carried out in completely randomized design with four replicates. Each experimental plot comprised one sapling in initial developmental stage. The herbicides did not cause saplings death, even though all of them showed phytotoxicity symptoms. Herbicide application reduced the leaf dry mass as follows: isoxaflutole, 20% of the species; bentazon, one of the species; and sethoxydim did not reduce leaf dry mass in any of the species.